PERTUMBUHAN DAN HASIL EMPAT VARIETAS TANAMAN KACANG HIJAU (Vigna radiata L.) PADA PEMBERIAN DOSIS PUPUK KANDANG AYAM DI TANAH ULTISOL - Candra, Robi; Sumardi, Sumardi; Hermansyah, Hermansyah (BPFP Universitas Bengkulu, 2020)
[GROWTH AND YIELD OF FOUR VARIETIES OF MUNG BEAN (Vigna radiata L.) PLANT ON DOSING OF CHICKEN MANURE FERTILIZER IN ULTISOL]. Ultisols generally have less favorable physical, chemical, and biological properties. Chicken manure is believed to be able to improve soil structure, increase water holding capacity, increase soil pH, increase cation exchange capacity, increase soil biological activity, and facilitate root penetration. This study aims to determine the optimum dose of chicken manure in increasing the growth and yield of four mung bean varieties in Ultisol. This research was conducted using a split-plot design. The doses of chicken manure (0 tons/ha, 10 tons/ha, 20 tons/ha, and 30 tons/ha) were placed in the main plots and mung bean varieties (Vima-1, Vima-2, Kutilang, and Murai) as children. plots with experimental plot units measuring 1 m x 2 m. This study aims to obtain the optimum dose of chicken manure on four varieties of mung bean plants and to find the varieties that have the best growth and yield of green bean plants in Ultisol. The results showed that the highest weight of 100 seeds was obtained from the Kutilang variety which was given chicken manure of 21.34 tons/ha with a maximum weight of 100 seeds of 8.82 g. The highest yield of seed/plant weight was obtained from the application of chicken manure 19.61 tons/ha with a yield of 15.43 g. Kutilang variety is the best variety compared to other varieties, with yields of seed weight/plant of 12 g.